English compound meaning predictability : an exploratory cross-linguistic study - Hien Pham, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Compound words are integral to the development of word knowledge in English. This study explored cross-linguistic similarities and differences in compound-meaning inference, focusing on the semantic relation between the modifier and head in noun-noun compounds. Semantic relation specifies how the meanings of the modifier and head are combined. Although some less-established compounds allow multiple semantic relation, causing ambiguity in meaning, L1 speakers of English typically prefer using semantic relation/meaning. This study investigated whether English L2 students would be able to identify the dominant semantic relation of ambiguous novel compounds (e.g., child art). Two groups of English L2 university students, a Thai L1 group and a Vietnamese L1 group, completed a multiple-choice format, compound-meaning inference task, in which they identified the dominant meanings, as preferred by a group of native speakers of English. Results indicated that the Thai L1 and Vietnamese L1 groups did not differ in their overall mean scores for the dominant meanings, although they demonstrated some differences at the item level. This study discusses the need for more cross-linguistic studies in compound words.